Access to Specialist Gastroenterology Care in Canada: The Practice Audit in Gastroenterology (PAGE) Wait Times Program. (2008) - Armstrong, David; Barkun, Alan NG; Chen, Ying; Daniels, Sandra; Hollingworth, Roger; Hunt, Richard H; Leddin, Desmond
Abstract : BACKGROUND: Canadian wait time data are available for the treatment of cancer and heart disease, as well as for joint replacement, cataract surgery and diagnostic imaging procedures. Wait times for gastroenterology consultation and procedures have not been studied, although digestive diseases pose a greater economic burden in Canada than cancer or heart disease. METHODS: Specialist physicians completed the practice audit if they provided digestive health care, accepted new patients and recorded referral dates. For patients seen for consultation or investigation over a one-week period, preprogrammed personal digital assistants were used to collect data including the main reason for referral, initial referral and consultation dates, procedure dates (if performed), personal and family history, and patient symptoms, signs and test results. Patient triaging, appropriateness of the referral and timeliness of care were noted. RESULTS: Over 10 months, 199 physicians recorded details of 5559 referrals, including 1903 visits for procedures. The distribution of total wait times (from referral to procedure) nationally was highly skewed at 91/203 days (median/75th percentile), with substantial interprovincial variation: British Columbia, 66/185 days; Alberta, 134/284 days; Ontario, 110/208 days; Quebec, 71/149 days; New Brunswick, 104/234 days; and Nova Scotia, 42/84 days. The percentage of physicians by province offering average-risk screening colonoscopy varied from 29% to 100%. DISCUSSION: Access to specialist gastroenterology care in Canada is limited by long wait times, which exceed clinically reasonable waits for specialist treatment. Although exhibiting some methodological limitations, this large practice audit sampling offers broadly generalized results, as well as a means to identify barriers to health care delivery and evaluate strategies to address these barriers, with the goals of expediting appropriate care for patients with digestive health disorders and ameliorating the personal and societal burdens imposed by digestive diseases.